Effects of Black Pepper (Piper nigrum L.) Chloroform Extract on the Enzymatic Activity and Metabolism of Escherichia coli and Staphylococcus aureus. (5th February 2018) - Chen, Wenxue; Zou, Lan; Chen, Weijun; Hu, Yueying; Chen, Haiming
Abstract : The chemical composition and antimicrobial mechanism of action of black pepper chloroform extract (BPCE) were investigated, as well as the potential antibacterial activities of BPCE against Escherichia coli and Staphylococcus aureus . The results showed that 1H-Cycloprop[e]azulen-7-ol, decahydro-1, 1, 7-trimethyl-4-methylene-, [1ar-(1a α, 4a α, 7 β, 7a, β, 7b α .)]- (8.39%) and 2-methylene-4, 8, 8-trimethyl-4-vinyl-bicyclo[5.2.0]nonane (6.92%) were identified as the two primary components of BPCE. The release of intracellular transaminases from bacteria after being incubated with BPCE revealed that the bacterial cell walls and membranes were degraded and that protein synthesis was inhibited to some extent. The inhibition of bacterial Na + /K + -ATPase activity upon the addition of BPCE also indicated an enhanced permeability of bacterial cell membranes. Moreover, an analysis of hexokinase and pyruvate kinase activities showed that BPCE affected the metabolic rate of glycolysis and disrupted the normal metabolism of bacteria. This phenomenon was supported by an observed accumulation of lactic acid (LA) in the treated bacterial cells. Overall, our results indicated that BPCE damaged bacterial cell walls and membranes, which was followed by a disruption of bacterial cell respiration.